Effects of e-cigarettes on human health: a narrative review of systemic evidence - Rusudan Vadatchkoria; Saina Ranjan; Hrithika Madireddy; Gaarnika Jha (Georgian Medical Journal, 2026)
Background: Electronic cigarettes (e-cigarettes) have become increasingly popular worldwide as alternative nicotine delivery systems and are often promoted as less harmful substitutes for conventional combustible cigarettes. Although they may reduce exposure to some toxic products of tobacco combustion, growing evidence indicates that e-cigarette aerosols are not biologically inert and may adversely affect multiple organ systems. Their long-term safety remains insufficiently understood. Aim: To evaluate current scientific evidence regarding the systemic health effects of e-cigarette use, assess their potential role in tobacco harm reduction, and identify knowledge gaps relevant to clinical practice and public health. Methods: This narrative review was based on a comprehensive analysis of peer-reviewed literature indexed in PubMed, Scopus, and Web of Science. Original studies, systematic reviews, experimental and clinical investigations, epidemiological and longitudinal studies, and international public health reports were critically evaluated. Results: Current evidence suggests that e-cigarette effects are systemic and extend beyond the respiratory tract, involving the cardiovascular, gastrointestinal, haematological, immune, reproductive, urinary, musculoskeletal, and nervous systems, as well as sleep regulation. The main mechanisms include oxidative stress, chronic inflammation, endothelial dysfunction, immune dysregulation, cellular injury, and nicotine dependence. Although e-cigarettes generally expose users to lower levels of many toxic compounds than conventional cigarettes, available evidence indicates that they cannot be considered risk-free. Their effectiveness as smoking cessation aids remains controversial, while dual use and persistent nicotine dependence represent significant public health concerns. Conclusions: E-cigarettes may contribute to tobacco harm-reduction strategies for selected adult smokers who completely switch from combustible cigarettes; however, their long-term systemic safety has not been established. A cautious, evidence-based approach is required to balance potential benefits against risks associated with prolonged nicotine exposure and systemic toxicity. Further high-quality longitudinal studies are needed to clarify long-term health outcomes and guide future clinical recommendations and public health policy. Keywords: electronic cigarettes; vaping; nicotine; toxicity; aerosol harm; organ systems; harm reduction